Perbedaan Abnormal Return Sebelum dan Sesudah Pemilihan Umum Gubernur DKI Jakarta Tahun 2017 - Sari, Luh Gede Hari Purnama; Gayatri, Gayatri (E-Jurnal Akuntansi; Vol 24 No 2 (2018)DO - 10.24843/EJA.2018.v24.i02.p22, 2018)
The General Election of DKI Jakarta Governor Year 2017 is a political events affecting the capital market. This study aims to determine abnormal return around the events and to determine the difference of abnormal return before and after the events. This study was conducted in companies incorporated the Compass Index 100 period February to July Year 2017. The samples are 92 companies, determined by nonprobability sampling method, especially purposive sampling technique. Research analysis technique is Chi-Square Test and Wilcoxon Signed Ranks Test. The result are that there is abnormal return around the events of General Election of Governor of DKI Jakarta Year 2017. There are differences of abnormal return before and after General Election of DKI Jakarta Governor Year 2017. The events contains information and make investors react. This research can prove efficient market theory of a half strong form as a representation of the market response to an event. Keywords: abnormal return, market reaction